Pediatric traumatic renal artery thrombosis: A single institution experience - Allen Zhong; Celia Short; Ryan Spurrier (Elsevier, 2022)
Traumatic renal artery thrombosis (RAT) is a rare injury that results in loss of ipsilateral renal perfusion. While described in adult populations, pediatric traumatic RAT has sparsely been investigated. We aimed to present 4 cases of pediatric traumatic RAT. All patients presented with unilateral RAT after blunt trauma with severe concurrent traumatic injuries. No patients received surgical or endovascular intervention or had any inpatient or outpatient complications related to RAT. One patient was discharged with anticoagulation (81mg aspirin) after initial presentation to an adult trauma center. Only one patient required anti-hypertensives in the setting of severe intracranial hemorrhage for 1 day in the ICU. Pediatric traumatic unilateral RAT in this cohort was not associated with hypertension or renal failure and did not require intervention, but more follow-up data is required to observe for longer term RAT-associated sequelae.